When Bible and science interact: teachers' pedagogic and value challenges in teaching religious minority students in higher education settings. Issue 5 (3rd July 2016) - Novis-Deutsch, Nurit; Lifshitz, Chen
ABSTRACT: The integration of highly religious minority students into institutions of higher education poses significant pedagogical and value challenges for students and teachers alike. We offer a framework for analyzing such challenges, distinguishing between practical concerns, identity issues and value conflicts. By contrasting a deficit perspective to 'Diversity as resource', we argue that the latter enables teachers to utilize a collaborative knowledge model in class, surmounting some of the value challenges involved. We present the case of ultra-orthodox students in Israel who have recently entered the gates of higher education for the first time in this society's history. We analyze the narratives of 30 lecturers who teach this population. Most of them adopt a deficit perspective and see their role as academic gatekeepers, minimally adjusting content and pedagogy. A smaller group fosters cross-cultural dialog via a 'Diversity as resource' perspective. These findings lead to recommendations for successfully teaching highly religious students.